2018
DOI: 10.1007/s40520-017-0886-5
|View full text |Cite
|
Sign up to set email alerts
|

Geriatricians and the older emergency general surgical patient: proactive assessment and patient centred interventions. Salford-POP-GS

Abstract: Increasing numbers of older patients require Emergency admission under General Surgery (EGS). This is a group of heterogeneous and often complex individuals with varying degrees of multimorbidity, polypharmacy, functional, mobility and cognitive impairment. Our article describes the benefits of comprehensive assessment coupled with patient-centred multiprofessional interventions and timely discharge planning. We discuss diverse service models and describe our experience in the planning, development and consoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Examination of the study population, their age, total hospital and ICU length of stay and their discharge disposition indicated that those identified as frail by the FRAIL scale were indeed a subset of patients that could benefit from early identification in the ED. Instituting interventions, such as geriatrics consultation and multidisciplinary evaluation including social work, at the point of triage in the ED is increasingly incorporated in patient centered care [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Examination of the study population, their age, total hospital and ICU length of stay and their discharge disposition indicated that those identified as frail by the FRAIL scale were indeed a subset of patients that could benefit from early identification in the ED. Instituting interventions, such as geriatrics consultation and multidisciplinary evaluation including social work, at the point of triage in the ED is increasingly incorporated in patient centered care [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…7 Abdominal surgical procedures such as colectomy, small-bowel resection, cholecystectomy, appendectomy, and others constitute~80% of all emergent surgeries performed in older patients. 23,24 The association of frailty and in-hospital complications after emergent general surgery in older patients was examined in a study published by Joseph et al 31 In this prospective study, 220 consecutive patients aged 65 years who presented to a single acute care surgery trauma center were enrolled. The mean age of the participants was 75.5 (7.7) years (56% men), and 37% were frail as determined by a modified 50-variable Rockwood Preadmission Frailty Index (ie, FI score 0.25).…”
Section: Emergent Surgerymentioning
confidence: 99%
“…Furthermore, older patients represented 28.8% of all major emergency general surgery cases, with partial colectomy, small-bowel resection, cholecystectomy, operative management of peptic ulcer disease, lysis of peritoneal adhesions, appendectomy, and laparotomy collectively accounting for 80% of all procedures, 80.3% of deaths, 78.9% of complications, and 80.2% of inpatient costs. 23,24 Given the importance of general surgery as a common and main therapeutic intervention in older patients, its associated risk of complications and other adverse clinical outcomes, it is paramount to develop reliable risk-stratification tools to aptly guide clinicians and patients in medical decision making when general surgery is offered as a treatment. A critical first step to achieving this goal is to determine whether frailty, a measure of physiologic reserve and vulnerability in older patients, is predictive of adverse clinical outcomes after general surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Multidisciplinary teams including geriatricians along with surgeons and anesthesiologists have been established so far in the orthogeriatric field, but there are very scant evidence on the effectiveness of such teams in oncological surgery [43][44][45][46]. Yet, we predict that, once established, such teams will successfully improve many clinical outcomes associated with solid tumor and their surgery, improving patient's functional status and quality of life.…”
Section: The Geriatrician's Clinical Standpointmentioning
confidence: 99%